Pengaruh Budaya Organisasi Kerja Terhadap Kinerja Tenaga Kesehatan Di Rumah Sakit Abdoel Wahab Sjahranie - Suwanto Suwanto; Dwi Ida Puspita Sari; Andik Supriyatno (Indonesian Journal of Wiyata Health Administration (IJWHA), 2021)
Culture is accepted by an organization as the foundation of the management system applied to it and as a guideline for the behavior of its members. A strong organizational culture helps employees clearly understand the tasks assigned by the organization and has a major influence on the performance of organizational members. HOSPITAL. This study used a cross-sectional study using a simple regression test with a significance level of 0.05. The population in this study were 90 civil servants administrative staff at Abdoel Whab Sjahranie Hospital. Respondents get a research tool in the form of a questionnaire or questionnaire to answer. The results of research with simple regression statistical tests show that culture. The organization includes commitment, consistency, adaptability, and mission which have a significant effect on employee performance. The conclusion of this study is that organizational culture has a strong significant influence on employee performance at Abdoel Wahab Sjahranie Hospital.